2009
DOI: 10.1164/rccm.200901-0115oc
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Colony-forming Cells from Preterm Infants Are Increased and More Susceptible to Hyperoxia

Abstract: Rationale: Preterm birth and hyperoxic exposure increase the risk for bronchopulmonary dysplasia (BPD), a chronic lung disease characterized by impaired vascular and alveolar growth. Endothelial progenitor cells, such as self-renewing highly proliferative endothelial colony-forming cells (ECFCs), may participate in vascular repair. The effect of hyperoxia on ECFC growth is unknown. Objectives: We hypothesize that umbilical cord blood (CB) from premature infants contains more ECFCs with greater growth potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
93
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(103 citation statements)
references
References 52 publications
4
93
0
4
Order By: Relevance
“…EPCs consist of diverse progenitor-like cell populations, including early-outgrowth EPCs and late-outgrowth endothelial colonyforming cells (ECFCs). Unlike early EPCs, ECFCs have an endothelial morphology, express endothelial markers, are highly proliferative, and exhibit a progenitor-like capacity for self-renewal [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…EPCs consist of diverse progenitor-like cell populations, including early-outgrowth EPCs and late-outgrowth endothelial colonyforming cells (ECFCs). Unlike early EPCs, ECFCs have an endothelial morphology, express endothelial markers, are highly proliferative, and exhibit a progenitor-like capacity for self-renewal [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Although the incidence and severity of respiratory distress syndrome have decreased with antenatal corticosteroid therapy and postnatal surfactant replacement, the overall incidence of BPD has been increasing. 3,4 BPD is predominantly characterized by persistent abnormalities of lung structure and arrested lung development, including impaired alveolar and vascular growth.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 BPD is predominantly characterized by persistent abnormalities of lung structure and arrested lung development, including impaired alveolar and vascular growth. 1,5 The pathogenesis of BPD is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…In the cord blood of preterm infants, EPC counts have been shown to be either similar to or increased versus full‐term infants, but studies of ECFC subtype proliferation and vessel formation have yielded contradictory results 54. Cord blood ECFC from preterm infants were shown to be particularly vulnerable to oxidant conditions (such as hyperoxia) with drastically impaired growth potential, disrupted nitric oxide/vascular endothelial growth factor signaling, accelerated cell senescence, as well as increased oxidative stress status 16, 17, 55. In addition, human fetal lung ECFC and newborn rat ECFC function are also impaired after high oxygen exposure (mimicking preterm birth conditions) 36.…”
Section: Discussionmentioning
confidence: 99%
“…However, preterm birth is associated with perinatal conditions that are deleterious for organ development, and often inherently prooxidative (including the major rise in po 2 occurring during the transition from fetal to extrauterine life) and proinflammatory in nature 14, 15. Importantly, studies have shown that EPC of preterm infants, more specifically the subpopulation of endothelial colony‐forming cells (ECFC), have an increased vulnerability to hyperoxia‐induced oxidative stress resulting in cell dysfunction 16, 17. ECFC, although highly present in the cord blood of newborn infants, are only found in very low quantities in the peripheral circulation of adults 12, 18, 19.…”
Section: Introductionmentioning
confidence: 99%